Inhibition of Thiamine Transport by Chloroethylthiamine in Escherichia coli - Iwashima, Akio (1972)
Chloroethylthiamine was found to inhibit an entrapment of thiamine as thiamine monophosphate by blocking thiamine monophosphokinase in the cytoplasm after thiamine was taken up by the cells of Escherichia coli.